The iPortfolio: measuring uptake and effective use of an institutional electronic portfolio in higher education - Von Konsky, Brian; Oliver, Beverley (ASCILITE, 2012)
An institutional electronic portfolio called the iPortfolio had over 17,000 subscribers one year after its introduction at an Australian university. This paper reports on a study to determine how students use these iPortfolio accounts, and factors leading to uptake and effective use. Self-assessed competence with technology skills, factors motivating uptake, and barriers to adoption were examined using an online survey completed by 554 students. Of these, 339 had an iPortfolio at the time they completed the survey. Survey results were examined in the context of usage patterns based on data automatically collected for operational and administrative purposes. No statistically significant difference to prior technology use or self-assessed competence with information technology was observed when comparing students with iPortfolio accounts to those without. Assessment was found to be the principal driver of iPortfolio uptake. However, about two-fifths (42.9%) of students agreed that they were likely to use iPortfolio in the future, even if it was not a course requirement. An additional 29.6% were neutral. Significant use of the iPortfolio to reflect on extracurricular activities was not observed. Improved employability outcomes were seen to be a benefit of iPortfolio adoption by about half (52%) of the students. Recommendation are made to promote iPortfolio uptake and encourage student reflection on 'lifewide' experiences that enhance employability and augment learning within the formal curriculum.